Digital Image Analysis Of Single Rectangular Slit Fraunhofer Diffraction Patterns - Yuri Yogaswara; Fourier Dzar Eljabbar Latief (Institut Teknologi Bandung, 2019)
Study of the single rectangular slit Fraunhofer diffraction pattern has been carried out through experiments. Data acquisition was done by manually measuring the distance of the bright and dark diffraction patterns using millimeter block paper and by means of digital images analysis of the diffraction patterns. The digital images were used to obtain the bright and dark intensity data of the pattern as the function of the distance from the center of the pattern. The process of obtaining the data was carried out as follows: image acquisition, image digitization, image quality enhancement, graphics plotting and chart normalization. The data processing is done analytically and computationally using ImageJ software. The results of the digital image analysis of diffraction patterns produce an intensity graph of the distance of the diffraction pattern (I-y chart). The results from the digital image analysis approach provide an alternative method that is more accurate in the process of calculating the physical magnitude of diffraction parameters such as the wavelength of the source. One of the advantages of this method is that intensity of the diffraction pattern can be visualized as a function of the distance from the center of the screen. Although accuracy of the calculation result is not very high, the magnitude of the intensity can be observed to decrease with increasing distance of the diffraction pattern to the center of the screen. The results of the calculation of the source wavelength by means of digital image analysis provides good results compared to the manual method using the millimeter block paper. The smallest mean error of the wavelength by means of digital image analysis is 1,72% and the manual method using the millimeter block paper is 3,84%. This method of measurement using digital image analysis can be used as an alternative for various position or distance-based measurement, such as the calculation of linear expansion coefficient with a single slit diffraction method.